Influence Comparison of Precursors on LiFePO4/C Cathode Structure for Lithium Ion Batteries - Luthfi Mufidatul Hasanah; Cornelius Satria Yudha; Soraya Ulfa Muzayanha; Diajeng Putri Suciutami; Atika Aulia Novita Sari; Inayati Inayati; Agus Purwanto (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
Electricity is the most energy demanded in this era. Energy storage devices must be able to store long-term and portable. A lithium ion battery is a type of battery that has been occupied in a secondary battery market. Lithium iron phosphate / LiFePO4 is a type of cathode material in ion lithium batteries that is very well known for its environmental friendliness and low prices. LiFePO4/C powder can be obtained from the solid state method. In this study the variables used were the types of precursors : iron sulfate (FeSO4), iron oxalate (FeC2O4) and FeSO4+charcoal. Synthesis of LiFePO4/C powder using Li:Fe:P at 1:1:1 %mol. Based on the XRD results, LiFePO4/C from FeSO4+charcoal shows the LiFePO4/C peaks according to the JCPDS Card with slight impurities when compared to other precursors. XRD results of LiFePO4/C with precursors of FeSO4 or FeC2O4 shows more impurities peaks. This LiFePO4/C cathode is paired with lithium metal anode, activated by a separator, LiPF6 as electrolyte. Then this arrangement is assembled become a coin cell battery. Based on the electrochemical results, Initial discharge capacity of LiFePO4/C from the FeSO4 precursor is 19.72 mAh/g, while LiFePO4/C with the FeC2O4 precursor can obtain initial discharge capacity of 17.99 mAh/g, and LiFePO4/C with FeSO4+charcoal exhibit initial discharge capacity of 21.36 mAh/g. This means that the presence of charcoal helps glucose and nitrogen gas as reducing agents.